Establishing a Shared Services Centre in Prague- SAP BSCE Study Case - Nguyen Ngoc, Huong; Pichanič, Mikuláš, 1942-; Sixta, Jaroslav; Vysoká škola ekonomická v Praze. Rektorát (2011)
The Thesis is conducted based on analysis of a business shared service centre, all factors to consider before the establishment, its scope, model, and the most important is to see advantages as well as to realize the shortcomings of this kind of business model. The country which is analyzed is the Czech Republic; more particular is the city of Prague; and the company is SAP Business Service Centre of Europe (BSCE). In this Thesis, first of all, the PEST (Political, Economic, Social and Technology) environmental analysis has been conducted. The work continues with the SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis of the company SAP AG, from which, we can see that opening a SAP BSCE is a part of SAP strategy which supposes to benefit the company. In order to establish the BSCE, the SAP management board has to consider the factors such as Organization, People, Processes and IT Infrastructure. After analyzing approximately 20 cities in Europe, SAP has chosen Prague as the best mix of quality and costs factors. SAP BSCE covers the functions of Human Resource and Finance and Administration, which provide services to internal and external customers of many countries in Europe, Middle East, and Africa. SAP BSCE has brought back many advantages such as cost-savings, high quality service, business availability and flexibility, and business transparency and legal compliance. On the other hand, there are still many short-comings, such as the high turn-over rate of staff, difficulties in harmonization and standardization of processes and IT infrastructure, and how to prove the quality of service. Despite these challenges, SAP BSCE has put efforts into trying to overcome these problems.
At the end of the Thesis, as per analysis of SAP financial results of business activities during the crisis, it is proven the setting up a shared service centre was a good decision of SAP and it paid off with the contribution to help SAP overcome the impacts of crisis.
Vedoucí práce: Mikuláš Pichanič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Rektorát, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses